THE APPLICATION OF MUSICAL INTELLIGENCE-BASED MATHEMATICS LEARNING ON PLANE SHAPE DISCUSSION - Ismah, Ismah; Prasetyo, Bayu Aji Eko (PATTIMURA UNIVERSITY, 2022)
In this study, Gardner's theory of multiple intelligences was used to conduct experimental research on several elementary school students at TPQ Al-Ikhwan Meruya Jakarta, Indonesia. The initial stage of this study was to classify the types of student intelligence using multiple intelligence instruments adopted from Shearer in 1997. Furthermore, learning strategies are applied to students according to the kind of intelligence. This study observed the differences in mathematics learning outcomes of students who have musical intelligence before and after the application of interactive learning media in the form of music containing a song with the title